Reintrepetation of Muhammad Syahrur's Limitation Theory on the Development of Islamic Economics - Retnowati, May Shinta; Dimyati Huda, Muhammad; Abd.Rahman, Zayyad (Qawanin: Jurnal of Economic Syaria Law, 2025)
The development of the Sharia economy and the financial system has increased, the amount of increase in the conventional economic sector is still the prima donna of the community, this is evidenced by the level of Sharia economic development which is still growing at 10% in the quarter of 2024. This is a big challenge for the existence of the Sharia Economy, because the community still views that the Sharia economic system is not flexible with what is needed by the community. In this study, the potential of Sharia economics is initiated that can be applied in accordance with the development of the times and anywhere according to the concept of Muhammad Syahrur's thought. The results of Muhamad Syahrur's thinking show that the limitation theory is able to offer an innovative and flexible approach regardless of Islamic principles and wise ethics to be an aspect of prudence so as not to sacrifice ethical and moral goals in muamalah activities. This study reveals Muhammad Syahru's thinking pattern literally from the limitations or hudud that is applied in the study of the field of Sharia economics. The results of Muhamad Syahrur's thinking show that the limitation theory is able to offer an innovative and flexible approach regardless of Islamic principles and wise ethics to be an aspect of prudence so as not to sacrifice ethical and moral goals in muamalah activities.